2019
DOI: 10.1177/2047487319885458
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable lifestyle risk factors and C-reactive protein in patients with coronary artery disease: Implications for an anti-inflammatory treatment target population

Abstract: Background Modifiable lifestyle risk factors (modRF) of coronary artery disease (CAD) are associated with increased inflammation represented by elevated C-reactive protein (CRP) levels. Lifestyle changes may influence the inflammatory burden in patients with CAD, relevantly modifying the target population for emerging anti-inflammatory compounds. Aims The aims of this study were to analyse the association of modRF and CRP levels in CAD patients, and to define a potential target population for anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…A recent study showed that 39.2% of patients with type 2 diabetes had RIR and the findings suggested that glycemic control, insulin resistance, non-LDL-C lipid variables and central obesity are implicated in RIR in patients with type 2 diabetes even with well-controlled LDL-C levels [ 33 ]. These findings support the observations that patients with high inflammatory burden could achieve an hs-CRP <2 mg/L by lifestyle modifications alone [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study showed that 39.2% of patients with type 2 diabetes had RIR and the findings suggested that glycemic control, insulin resistance, non-LDL-C lipid variables and central obesity are implicated in RIR in patients with type 2 diabetes even with well-controlled LDL-C levels [ 33 ]. These findings support the observations that patients with high inflammatory burden could achieve an hs-CRP <2 mg/L by lifestyle modifications alone [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…alcohol, body mass index, diet, physical activity, smoking and waist-to-hip ratio). 7 Supporting the INTERCATH cohort results of Blaum et al, 1 studies of lifestyle modifications in the USA have also reported beneficial cardiovascular outcomes, suggesting that the effects are not unique to the former population. 4,23 These studies also infer, but did not directly prove, an association between high CRP levels and CAD.…”
mentioning
confidence: 72%
“…In the research article 'Modifiable lifestyle risk factors and CRP in patients with coronary artery diseaseimplications for an anti-inflammatory treatment target population', Blaum et al 1 addressed the relevant and important association between inflammation and serum levels of C-reactive protein (CRP) in a hospital-based cohort study of patients with coronary artery disease (CAD) in Germany. Their results present a promising approach in the management of CAD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is independently associated with peak oxygen uptake (VO 2 peak) and total work capacity (TWC), accounting for nearly 70% of the age-related decay (Marchionni et al, 2000). Controlling life risk factors including physical inactivity and sedentary behaviors might be an effective method to reduce global mortality and morbidity in patients with CVD (Fletcher et al, 2018;Blaum et al, 2019;Lavie et al, 2019). Lifelong (>25 years) exercise may alleviate a sedentary-and aging-induced decrease in systolic longitudinal strain (LS) through improving left ventricular (LV) diastolic filling (Howden et al, 2018).…”
Section: Exercise and Age-related MImentioning
confidence: 99%